Pengaruh Penerapan Sistem Informasi Akuntansi Terhadap Tata Kelola Keuangan Di BPJS Ketenagakerjaan Cabang Meulaboh - Fitria, Delia (Journal of Economics, Bussiness and Management Issues, 2023)
The  purpose  of  this  research  is  to  determine  the  effect  of  implementing  an  accounting information  system on  financial governance  at  BPJS  Employment  Meulaboh  Branch.  Of course, the inappropriate implementation of a technology-based accounting information system is the cause of delays in the process of disbursing guarantee funds. A similar condition also occurred during the COVID-19 period, when BPJS Employment had difficulty managing its finances due to the lack of a good accounting information system. By utilizing unstructured interviews and direct observation at the Meulaboh branch of BPJS Employment, the researcher used qualitative descriptive methods in the research. The research findings show that  good  financial governance  has  a beneficial  influence  on  the  accounting  information system, this can be seen from the existence of the Fun Shop at BPJS Employment Meulaboh Branch. The reason is, Lapak Asik makes it easy to distribute funds for participants and provides transparency regarding the procedures for distributing funds at the Meulaboh branch of BPJS Employment. The obstacle experienced in implementing the accounting information system in the form of Lapak Asik is that employees cannot differentiate between genuine and fake files because all files are sent in files, and there are still many participants who are technologically illiterate.